Management of sialorrhoea in motor neuron disease: A survey of current UK practice. Issue 7 (December 2013) - Hobson, Esther V.; McGeachan, Alexander; Al-Chalabi, Ammar; Chandran, Siddharthan; Crawley, Francesca; Dick, David; Donaghy, Colette; Ealing, John; Ellis, Cathy M.; Gorrie, George; Hanemann, C. Oliver; Harrower, Timothy; et al.
Abstract: Our objective was to better understand UK-wide practice in managing sialorrhoea in motor neuron disease among specialist clinicians. We used a survey of neurologists in the UK with a special interest in motor neuron disease designed to establish clinicians' attitudes towards treatment options and resources for sialorrhoea management. Twenty-three clinicians replied, representing 21 centres. Sixteen centres were specialist MND Care Centres. Clinicians estimated seeing a total of 1391 newly diagnosed patients with MND in 2011. One hundred and ninety-three patients were described. Forty-two percent of patients reviewed in clinicians' last clinic had sialorrhoea and 46% of those with sialorrhoea had uncontrolled symptoms. Clinicians' preferred drugs were hyoscine patches, amitriptyline, carbocisteine and botulinum toxin. Botulinum toxin was used in 14 centres. Risk of dysphagia and staff skills were identified as the main barriers to botulinum toxin use. This survey suggests that there may be as many as 1700 patients with MND in the UK who have symptoms of sialorrhoea and that symptoms may be poorly controlled in nearly half. Treatment strategies varied, reflecting the lack of evidence based guidelines. The use of specialist treatments was influenced by local infrastructure. This study highlights the need for further work to develop evidence based guidance.